Study on pool combustion of tire wasted fuel, plastic fuel and diesel fuel - Ezzad, Ezani (2012)
This thesis is study about the characteristic of flame for plastic and tire fuel compare with diesel fuel. Three kind of fuel were experimented by using combustion chamber. The measurement of fuel considers particulate matter measurement and exhaust flame temperature. The parameter measurements in this experiment are temperature, height, color of the flame and particulate matter. This result shows that plastic fuel has the higher height and temperature of flame compare with tire and diesel fuel. However, plastic fuel shows lower in particulate matter and dry soot compare with tire and diesel. It can conclude that plastic fuels high possibility applied as a one of alternative fuel for internal combustion engine.